The daughters' war - Buehlman, Christopher (Buehlman, Christopher. Blacktongue, 2024)
"Galva -- Galvicha to her three brothers, two of whom the goblins will kill -- has defied her family's wishes and joined the army's untested new unit, the Raven Knights. They march toward a once-beautiful city overrun by the goblin horde, accompanied by scores of giant war corvids. Made with the darkest magics, these fearsome black birds may hold the key to stopping the goblins in their war to make cattle of mankind. The road to victory is bloody, and goblins are clever and merciless. The Raven Knights can take nothing for granted -- not the bonds of family, nor the wisdom of their leaders, nor their own safety against the dangerous war birds at their side. But some hopes are worth any risk"--